Pengaruh Laba, Arus Kas, dan Likuiditas Terhadap Financial Distress : Studi Kasus pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Nurhidayah Nurhidayah; Lihan Rini Puspo Wijaya; Endah Yuni Puspitasari (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Financial distress is a phase of decline in the company's financial condition before liquidation or bankruptcy. Based on the results of the BPS survey in 2020, transportation and logistics companies experienced a decrease in revenue of 90.34% which was the third highest decline among all industries. This study aims to determine the effect of profit, cash flow, and liquidity on the occurrence of financial distress in transportation and logistics companies listed on the Indonesia Stock Exchange in 2019-2022. This study used a population of 30 companies, and a sample of 11 companies with purposive sampling method. This study uses secondary data and is analyzed using Partial Least Square (PLS) with the SmartPLS version 3.29 application. The results of this study indicate that earnings have a positive effect on financial distress, cash flow has no effect on financial distress, and liquidity has a positive effect on financial distress. These results emphasize the importance of effective earnings and liquidity management in reducing the risk of financial distress, especially in times of crisis.